2017
DOI: 10.1016/j.bbamcr.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic autophagy deficiency on skeletal muscle apoptotic signaling, morphology, and function

Abstract: Autophagy is a catabolic process that targets and degrades cytoplasmic materials. In skeletal muscle, autophagy is required for the control of mass under catabolic conditions, but is also basally active in the maintenance of myofiber homeostasis. In this study, we found that some specific autophagic markers (LC3-I, LC3-II, SQSTM1) were basally lower in glycolytic muscle compared to oxidative muscle of autophagy competent mice. In contrast, basal autophagic flux was higher in glycolytic muscle. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…We speculate the significant increase of autophagy in the soleus but decrease in the EDL may have contributed, at least in part, to the muscle atrophy and dysfunction observed in HFpEF. Interestingly, previous data have shown that autophagic flux differs between oxidative and glycolytic muscles, which supports the suggestion that HFpEF could modulate this process in a fiber-dependent manner [20]. Moreover our findings also suggest that HFpEF could induce muscle alterations in both a fiber-and time-dependent manner determined by disease progression.…”
Section: Skeletal Muscle Dysfunction In Hfpef: Oxidative Vs Glycolyticsupporting
confidence: 91%
“…We speculate the significant increase of autophagy in the soleus but decrease in the EDL may have contributed, at least in part, to the muscle atrophy and dysfunction observed in HFpEF. Interestingly, previous data have shown that autophagic flux differs between oxidative and glycolytic muscles, which supports the suggestion that HFpEF could modulate this process in a fiber-dependent manner [20]. Moreover our findings also suggest that HFpEF could induce muscle alterations in both a fiber-and time-dependent manner determined by disease progression.…”
Section: Skeletal Muscle Dysfunction In Hfpef: Oxidative Vs Glycolyticsupporting
confidence: 91%
“…; Paré et al . ). Fibre type changes in response to our short protocol of CCA (3 h day −1 , 9 days) are unlikely to confound the results of this study, since a greater volume and time of stimulation is required to produce a shift in myosin heavy chain expression (Putman et al .…”
Section: Discussionmentioning
confidence: 97%
“…fast vs. slow) exhibit differences in autophagy/mitophagy turnover. Some studies have concluded that oxidative fibres have higher rates of flux (Lira et al 2013), while others have noted greater rates in predominantly glycolytic muscle (Mofarrahi et al 2013;Paré et al 2017). Fibre type changes in response to our short protocol of CCA (3 h day −1 , 9 days) are unlikely to confound the results of this study, since a greater volume J Physiol 596.16 and time of stimulation is required to produce a shift in myosin heavy chain expression (Putman et al 2001), and our previous work has documented enhanced fatigue resistance, but no change in half-relaxation time or time to peak tension in young or aged skeletal muscle following this CCA protocol ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein degradation in skeletal muscle is mainly controlled by two proteolytic systems, namely ubiquitin proteasome system (UPS) and autophagy-lysosome system (ALS). Several studies have shown that autophagy is required for the control of skeletal muscle mass under catabolic conditions and plays an important role in maintaining the homeostasis and integrity of skeletal muscle [ 63 ], especially the autophagy at the appropriate level. Previous studies have proved the importance of autophagy in skeletal muscle of Atg7 gene knockout rats, and autophagy inhibition can lead to muscle atrophy and myopathy [ 64 ].…”
Section: High Altitude Training Improves the Function Of Skeletal mentioning
confidence: 99%
“…Under the basal autophagy, slow-twitch muscle fibers are obviously higher than hybrid fibers and fast-twitch muscle fibers [ 22 ]. Compared with oxidative muscle, specific autophagic markers (LC3-I, LC3-II, and SQSTM1) are basally lower, but basal autophagic flux is higher in glycolytic muscle [ 63 ].…”
Section: High Altitude Training Improves the Function Of Skeletal mentioning
confidence: 99%